The Use of Teaching Aids in Informal Education at the Bethel Religious Institution - Leorince Leorince; Aser Lasfeto; Yuel Sumarno (Universitas Negeri Padang, 2023)
Educational creativity of religious institutions in the post-covid-19 pandemic is still considered lacking, because teachers seem to only give stories without any creativity in them, especially with the use of relatively ancient methods, making children in virtual classes extremely bored and unwilling to listen to the material presented. every Sunday. This study aims to develop the creativity of all Bethel religious teachers who will face even more severe challenges. This study uses a library research method by carrying out a descriptive qualitative approach where the data obtained comes from sources in the form of books, scientific journals and scientific articles, so that this research is successful where teachers can build the creativity of Sunday school teachers by doing, as follows: (i) teachers can create classes creatively, (ii) the puppet stage is very effective if it is carried out in a Bethel religious institution virtually with the help of the zoom platform and (iii) teach at this institution although it is virtual, it is still relevant to the conditions in this digital era.